LEADERSHIP DIGITAL: SHIFT PARADIGM AND ORGANIZATIONAL ADAPTATION CAPABILITY - Yanita; Siti Nurhasanah; Zilla Syabrina Putri; Shintya Anggraini; Dwi Wulan Br Pardede; Alya Rahmi; Aulia Yunita Khairani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Acceleration Industry 4.0 demands deconstruction radical against paradigm leadership traditional Which rigid And Hierarchical. This study aims to analyze the paradigm shift towards digital leadership and identify organizational adaptation capabilities to system transformation. The method used is a comparative literature study. Which integrated with analysis studies case relatedresistance employee to technology new. Results Research shows that traditional leadership triggers bureaucratic stagnation and reduces functional efficiency. In contrast, digital leadership has been shown to increase operational efficiency through three main pillars: governance communication transparent horizontal communication, data-driven decision-making, and the creation of an agile work environment. Case analysis demonstrates that cultural barriers in the form of internal resistance can be optimally resolved through digital leadership interventions combined with a situational approach. Leader flexibility in mapping follower readiness levels, digital role modeling, and persuasive education are key to mitigating psychological conflict. Integrationtechnology in lower control leadership digital proven real accelerate curve adoption system in order to improve organizational performance sustainably.